United States history 1877 to the present - Lapsansky-Werner, Emma J.; Levy, Peter B.; Roberts, Randy; Taylor, Alan (Pearson, 2016)
Industry and immigration (1865-1914) -- Challenges in the late 1800s (1865-1900) -- America comes of age (1890-1920) -- World War I and the 1920s (1914-1929) -- The Great Depression and the New Deal (1928-1941) -- World War II (1931-1945) -- Postwar America (1945-1960) -- Civil rights and reform in the 1960s (1945-1968) -- The Vietnam War era (1954-1975) -- An era of change (1960-1980) -- America in the 1980s and 1990s (1980-1999) -- America in the twenty-first century (2000-today) -- United States Constitution -- Primary sources -- Declaration of Independence -- 21st century skills -- Atlas -- Glossary